MODEL OF IMPACT PARENTAL FACTORS THAT INFLUENCE EXTERNALIZED AND INTERNALIZED PROBLEMS IN CHILDREN - Mendoza Nápoles , Christian Alberto; Maldonado Santos, Elsa Beatriz (Revista Electrónica de Psicología Iztacala, 2024)
A study was conducted to create a model of parenting, which explains different parental factors as exogenous variables to explain internalized and externalized problems in their sons and daughters. The sample was taken randomly in different elementary schools. An acceptable model that explains the relationship of the aforementioned variables was obtained. Results are discussed based on the gaps that existed in the theory of Diana Baumrid, respect to the model that was created to explain the aging in Ciudad Juárez, Chihuahua, also is discussed on the basis of other research carried out by measuring the variables in question. Two models were also developed for temperament variable, because for this variable there is a discussion in the literature as mediatory variable in rearing styles. A contrast was developed between the results of this study and previous studies related to this one.